2017
DOI: 10.4317/jced.53852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of home bleaching agents on surface microhardness of different glass-ionomer cements containing hydroxyapatite

Abstract: BackgroundHome bleaching agents may exert some negative effects on surface hardness of restorative materials such as glass-ionomer cements (GICs). Since some studies have shown that some components such as hydroxyapatite (HA), as a bioactive glass, can improve the mechanical properties of dental materials, the effect of bleaching agents on surface hardness of GICs containing hydroxyapatite is questionable. This study was designed to evaluate the effect of home bleaching agents on the surface hardness of two di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…The carbamide peroxide breaks down into hydrogen peroxide and urea. Hydrogen peroxide causes oxidation by generating free radicals and might induce the breaking of polymer chains (21). Furthermore, free radicals can affect the resin-filler interface and cause filler-matrix debonding (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbamide peroxide breaks down into hydrogen peroxide and urea. Hydrogen peroxide causes oxidation by generating free radicals and might induce the breaking of polymer chains (21). Furthermore, free radicals can affect the resin-filler interface and cause filler-matrix debonding (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The surface roughness of all materials used in this study was increased, but the increase in BC and VE was statistically significant. A large particle size can increase the microporosity in the structure (21,32). The increase in the surface roughness of BC can be explained by its larger particle sizes (<1μm) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…These materials were developed by adding resin monomers to GICs, resulting in much better esthetics, higher mechanical and handling properties, and higher bond strength to enamel and dentin. Another shortcoming of the conventional glass ionomer cements (CGICs) is their low mechanical strength [ 8 ]. The main reasons for the application of zirconia as a filler are its good chemical and dimensional stability, high toughness and mechanical strength, and a Young’s modulus similar to that of stainless steel alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Considering the high biocompatibility of hydroxyapatite, some researchers have made attempts to evaluate the effects of incorporating hydroxyapatite powder into restorative dental materials such as GICs. [811121314] The interaction between GICs and hydroxyapatite takes place through carboxylate groups in the polyacid structure. It has been reported that hydroxyapatite incorporation into GICs may improve the mechanical properties of GICs.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the bond strength of GIC to the tooth structure can also occur due to similarity of hydroxyapatite to the structure of enamel and dentin. [1213]…”
Section: Introductionmentioning
confidence: 99%